Effect of Preparation Condition of TiO𝟐 Film and Experimental Condition on CO𝟐 Reduction Performance of TiO𝟐 Photocatalyst Membrane Reactor - Akira Nishimura; Yuki Okano; Masafumi Hirota; Eric Hu (International Journal of Photoenergy)
It was previously reported that CO2 could be reduced into CO, CH4, and so forth, which can be used as fuels, by TiO2 as the photocatalyst under UV radiation. To increase the concentration of fuel and improve CO2 reduction performance on TiO2 photocatalyst, a membrane reactor composed of TiO2 and gas separation membrane prepared by sol-gel and dip-coating method has been built. Factors such as rising speed (RS) in the dip-coating process and the timing and amount of water injected in the membrane reactor in CO2 reduction experiment have been investigated. As a result, the largest amount of TiO2 film is obtained for RS=0.66 mm/s among various RS conditions investigated in this study. According to CO2 reduction experiment by gas circulation type reactor, too much water which cannot be consumed in CO2 reduction process would not help improving the CO2 reduction performance.